Using a heterodyne vibrometer in combination with pulse excitation for primary calibration of ultrasonic hydrophones in amplitude and phase. (14th June 2017) - Weber, Martin; Wilkens, Volker
Abstract: A high-frequency vibrometer was used with ultrasonic pulse excitation in order to perform a primary hydrophone calibration. This approach enables the simultaneous characterization of the amplitude and phase transfer characteristic of ultrasonic hydrophones. The method allows a high frequency resolution in a considerably short time for the measurement. Furthermore, the uncertainty contributions of this approach were investigated and quantified. A membrane hydrophone was calibrated and the uncertainty budget for this measurement was determined. The calibration results are presented up to 70   MHz . The measurement results show good agreement with the results obtained by sinusoidal burst excitation through the use of the vibrometer and by a homodyne laser interferometer, with RMS deviation of approximately 3 % –4% in the frequency range from 1 to 60   MHz . Further hydrophones were characterized up to 100   MHz with this procedure to demonstrate the suitability for very high frequency calibration.